Studi Pengaruh Kecepatan Motor Dan Jumlah Bilah Pisau Terhadap Hasil Potongan Rumput - Hendra Widiyantoro; Ikhwanul Qiram; Dewi Sartika (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2021)
Unwanted grass growth on land will cause problems for humans. Generally, the sickle is a tool that is often used to cut grass. The use of a sickle has several disadvantages, namely using manual labor, in some cases there is a narrow-angle that makes it impossible to cut with a sickle. This study uses variations of 2, 3, and 4 blades with motor rotation speeds of 666 RPM, 1713 RPM, and 3454 RPM. The data collection method is done by determining the mass of grass by 25 grams, then the grass is arranged and moved closer to the blade with a cutting time of 10 seconds. The shortest cut grass results were obtained on the number of blades 4 with a motor rotation speed of 3454 RPM, which is 10.92 mm. The difference in mass of grass clippings in the variation of blade 4 with RPM 1 and 3, which is 4 grams, indicates the overall cut grass Keywords: blade, motor rotation speed, grass cutted